(untitled) (Revista Cientifica Ingenio Magno, 2022)
Abstract—The axon jump platform used in sports bioengineering was used in this research for the objective of correlating lower body power and agility of university field tennis players from the city of Tunja through the Illinois and Bosco test. In the first, two tests were carried out and the time averaged was calculated. In the last, three jumps were used: Squat Jump, Countermovement and Abalakov, calculating average height, flight time and distance. Power was determined to be related to agility. The statistical analysis showed that there is no correlation between power and agility because the P-value is equal to 0.184 = 18.4% which is greater than 0.05 = 5%, consequently the null hypothesis is accepted and it is concluded that between agility and power is not correlated in court tennis players. Observing the results, it is recommended to work the workouts doing work on agility and power of the lower body, due to the low results obtained in the Bosco and agility tests, tennis being considered as a sport where changes of direction are essential. for the competition. Lately, physical aspects are being investigated using technology to monitor the athlete, being objective with the physical capacities to improve. Therefore, training these aspects could help with this goal.